Analysis of Overweight, Obesity, Physical Activity and Self-Estimation of Children in the Metropolitan Area of the Educational Region of Panama City, Panama - Ambulo Arosemena, Graciela; González Salina, Margarita; Montenegro, Raúl; Brooks, Yileika; Bonilla, Margarita; Camarena, Melissa; Moreno, Yoselyn (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2020)
The high levels of overweight and obesity that produce diabetes, hypertension, and other chronic diseases are a public health threat that starts from childhood through the adult age, altering a person´s quality of life directly. The purpose of this study is to determine the levels of overweight and obesity, the levels of physical activity and self-esteem of children aging 9 to 13 years, in educational establishments from the center of Panama City, Panama. Thirteen (13) educational centers participated pertaining to eight (8) territories from the capital of the country, where 748 students were evaluated. The instruments used to measure these variables were the measuring rod, the weight scale to measure the body mass index, the PAQ-C survey to measure the physical activity, and LAWSEQ to measure self-esteem in children. The studied population showed 17% of the students to be overweight, 13% obese, 70.05% with moderate physical activity, and 25.67% with low levels of physical activity. As far as self-esteem is concerned, 50.5% showed average self-esteem and 44% low self-esteem. In conclusion, it is important to perform physical activities as prevention and attention actions to obesity, overweight, and improvement of self-esteem. The analysis of the results indicates a higher prevalence of obesity in girls, and greater levels of physical activity in boys, in the case of self-esteem, age plays an important role in personal perception, especially in the female sex.